Roles of Trait Mindfulness in Behavioral Activation Mechanism for Patients With Major Depressive Disorder - Takagaki, Koki; Ito, Masaya; Takebayashi, Yoshitake; Nakajima, Shun; Horikoshi, Masaru (Frontiers in Psychology, 2020)
Behavioral activation and mindfulness have both been shown to engender improvement of functional impairment in patients with major depressive disorders. In behavioral activation, the practice of engaging with the direct experience of the present moment is central, especially when targeting avoidance. Consequently, mindfulness affects changes of avoidance in behavioral activation. This study was designed to assess exploratory relations among trait mindfulness, avoidance, and functional impairment in behavioral activation mechanism for depression. For 1042 participants with depression only or for depression with anxiety disorders, we used structural equation modeling to examine relations among trait mindfulness, avoidance, and functional impairment. Trait mindfulness non-reactivity, non-judging, and acting with awareness have a direct negative effect on avoidance. Trait mindfulness non-reactivity, trait non-judging, and trait acting with awareness had indirect negative effects on functional impairment. Results show that each trait mindfulness facet exhibited a distinct pattern of relations with avoidance and impairment.